Techniques for the detection of autophagy in primary mammalian cells - Puleston, D; Phadwal, K; Watson, A; Soilleux, E; Chittaranjan, S; Bortnik, S; Gorski, S; Ktistakis, N; Simon, A (Cold Spring Harbor Laboratory Press, 2015)
Autophagy is a lysosomal catabolic pathway responsible for the degradation of cytoplasmic constituents. Autophagy is primarily a survival pathway for recycling cellular material in times of nutrient starvation, and in response to hypoxia, endoplasmic reticulum stress, and other stresses, regulated through the mammalian target of rapamycin pathway. The proteasomal pathway is responsible for degradation of proteins, whereas autophagy can degrade cytoplasmic material in bulk, including whole organelles such as mitochondria (mitophagy), bacteria (xenophagy), or lipids (lipophagy). Although signs of autophagy can be present during cell death, it remains controversial whether autophagy can execute cell death in vivo. Here, we will introduce protocols for detecting autophagy in mammalian primary cells by using western blots, immunofluorescence, immunohistochemistry, flow cytometry, and imaging flow cytometry.